Pratiques d’élevage dans la ferme expérimentale de Hassi-Mamèche et leurs effets sur les caractéristiques physico-chimiques et microbiologiques du lait frais - BOUABSA SULTANA, FATIMA (My University, 2022)
Milk, intended for human consumption, is the integral product of the total and uninterrupted milking of a healthy, well-nourished and not overworked dairy female. Contaminated, it can be a vector for the transmission of pathogenic germs to humans and can present a risk to human health. Thus, the objective of this study is to assess its physico- chemical quality on the one hand, and to highlight the relationship between the different milkinghygienetechniques and the existing flora in raw milk. somewhereelse. Thisstudy was carried out during the period of April-June 2022 on the raw milk of dairy cattle from the experimental farm of Hassi Maméche. During the physico-chemical study, we measured the temperature, the pH, the density, the dry matter, the freezing point. For the microbiological study, we were interested in counting the total aerobic mesophilic flora, faecal and total coliforms, Staphylococcus aureus, Streptococci "D" and sulphite-reducing clostridium The results of our study show the absence of sulfito-reducing clostridium in the raw milk sample, but a significant load of total aerobic mesophilic flora at 30°C in the absence of compliance with milking hygiene rules, i.e. 1.64.106 cfu/ml. Good husbandry practices to obtain raw milk of good sanitary quality for presentation to the consumer in its fresh state and for use in the dairy industry, especially with raw milk. Key words: Pathogenic germs, raw milk, milking, physico-chemical study, microbiological study.
Keywords: Germes pathogènes; lait cru; traite; étude physico-chimique; étude microbiologique